Changes in Brain-Derived Neurotrophic Factor Expression Influence Sleep–Wake Activity and Homeostatic Regulation of Rapid Eye Movement Sleep. Issue 2 (20th November 2017) - Garner, Jennifer M; Chambers, Jonathan; Barnes, Abigail K; Datta, Subimal
Abstract: Study Objectives: Brain-derived neurotrophic factor (BDNF) expression and homeostatic regulation of rapid eye movement (REM) sleep are critical for neurogenesis and behavioral plasticity. Accumulating clinical and experimental evidence suggests that decreased BDNF expression is causally linked with the development of REM sleep-associated neuropsychiatric disorders. Therefore, we hypothesize that BDNF plays a role in sleep–wake (S–W) activity and homeostatic regulation of REM sleep. Methods: Male and female wild-type (WT; BDNF +/+) and heterozygous BDNF (KD; BDNF +/−) rats were chronically implanted with S–W recording electrodes to quantify baseline S–W activity and REM sleep homeostatic regulatory processes during the light phase. Results: Molecular analyses revealed that KD BDNF rats had a 50% decrease in BDNF protein levels. During baseline S–W activity, KD rats exhibited fewer REM sleep episodes that were shorter in duration and took longer to initiate. Also, the baseline S–W activity did not reveal any sex difference. During the 3-hour selective REM sleep deprivation, KD rats failed to exhibit a homeostatic drive for REM sleep and did not exhibit rebound REM sleep during the recovery S–W period. Conclusion: Interestingly, both genotypes did not reveal any sex difference in the quality and/or quantity of REM sleep. Collectively, these results, for the first time, unequivocally demonstrate that an intact BDNF system in both sexes is a critical modulator for baseline and homeostatic regulation of REM sleep. This study further suggests that heterozygous BDNF knockdown rats are a useful animal model for the study of the cellular and molecular mechanisms of sleep regulation and cognitive functions of sleep.